2023
DOI: 10.1038/s41467-023-37952-5
|View full text |Cite
|
Sign up to set email alerts
|

The small and large intestine contain related mesenchymal subsets that derive from embryonic Gli1+ precursors

Abstract: The intestinal lamina propria contains a diverse network of fibroblasts that provide key support functions to cells within their local environment. Despite this, our understanding of the diversity, location and ontogeny of fibroblasts within and along the length of the intestine remains incomplete. Here we show that the small and large intestinal lamina propria contain similar fibroblast subsets that locate in specific anatomical niches. Nevertheless, we find that the transcriptional profile of similar fibrobl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 89 publications
2
28
0
Order By: Relevance
“…GI fibroblast heterogeneity has been under intensive investigation in recent years (Brügger et al, 2020;Deng et al, 2022;Jasso et al, 2022;Kinchen et al, 2018;Kraiczy et al, 2023;Manieri et al, 2023;McCarthy, Manieri, et al, 2020;Paerregaard et al, 2023) We found that antral fibroblasts clustered similarly to intestinal and colonic fibroblasts, including the formation of Wnt and Bmp gradients (Brügger et al, 2020;McCarthy, Manieri, et al, 2020) but with differences in specific marker expression: for example, in the gastric mucosa Cd81 was expressed across all fibroblast subsets, as opposed to intestinal and colonic fibroblasts where…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…GI fibroblast heterogeneity has been under intensive investigation in recent years (Brügger et al, 2020;Deng et al, 2022;Jasso et al, 2022;Kinchen et al, 2018;Kraiczy et al, 2023;Manieri et al, 2023;McCarthy, Manieri, et al, 2020;Paerregaard et al, 2023) We found that antral fibroblasts clustered similarly to intestinal and colonic fibroblasts, including the formation of Wnt and Bmp gradients (Brügger et al, 2020;McCarthy, Manieri, et al, 2020) but with differences in specific marker expression: for example, in the gastric mucosa Cd81 was expressed across all fibroblast subsets, as opposed to intestinal and colonic fibroblasts where…”
Section: Discussionmentioning
confidence: 76%
“…GI fibroblast heterogeneity has been under intensive investigation in recent years (Kinchen et al 2018;Brügger et al 2020;Deng et al 2022;Jasso et al 2022;Paerregaard et al 2023;Kraiczy et al 2023) with little data on gastric fibroblasts (Kim et al 2020). We found that antral fibroblasts clustered similarly to intestinal and colonic fibroblasts, including the formation of Wnt and Bmp gradients (Brügger et al, 2020;McCarthy, Manieri, et al, 2020) but with differences in specific marker expression: for example, in the gastric mucosa…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Mesenchymal cells that were localized in the pores of the membrane, separating the top and bottom channel, were detected in all media conditions, demonstrating their capacity to migrate from the top to the bottom channel (Figure S3C). The localization of mesenchymal cells relative to intestinal epithelial cells may reflect their natural position in the human small intestine, where (myo)fibroblasts form a supportive layer directly under the intestinal epithelial barrier 22,23 . Mesenchymal cells were most prominent in the EM condition, whereas they were reduced and restricted to the bottom channel in the EM-DM condition and almost depleted in the DM condition (Figures 2A, S3A and S3D).…”
Section: Epithelial and Mesenchymal Cells Self-organize And Different...mentioning
confidence: 99%